2022
DOI: 10.1515/med-2021-0405
|View full text |Cite
|
Sign up to set email alerts
|

Gene signature to predict prognostic survival of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) has a high incidence and poor prognosis and is the second most fatal cancer, and certain HCC patients also show high heterogeneity. This study developed a prognostic model for predicting clinical outcomes of HCC. RNA and microRNA (miRNA) sequencing data of HCC were obtained from the cancer genome atlas. RNA dysregulation between HCC tumors and adjacent normal liver tissues was examined by DESeq algorithms. Survival analysis was conducted to determine the basic prognostic indicato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Previous studies have found that both protein and mRNA expression of DKC1 was higher in HCC than in non-cancerous liver tissues and was associated with advanced clinical stage and poor prognosis ( Liu et al, 2012 ; Ko et al, 2018 ; Zhang et al, 2021b ; Li et al, 2022a ). As for RNA-independent PUSs, their roles in HCC have rarely been explored.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have found that both protein and mRNA expression of DKC1 was higher in HCC than in non-cancerous liver tissues and was associated with advanced clinical stage and poor prognosis ( Liu et al, 2012 ; Ko et al, 2018 ; Zhang et al, 2021b ; Li et al, 2022a ). As for RNA-independent PUSs, their roles in HCC have rarely been explored.…”
Section: Discussionmentioning
confidence: 96%
“… 20 A prognostic gene model consisting of four genes, including SAPCD2, was constructed to predict the OS of HCC patients. 21 SAPCD2 exhibited increased expression in late stage HCC, which added to the evidence that SAPCD2 performs a critical function in HCC.…”
Section: Discussionmentioning
confidence: 75%
“…Hepatocellular carcinoma (HCC) is a malignant tumor generating from liver cells, which is very common in Asia including China, accounting for approximately 80% of all liver cancer types [1,2]. At present, a growing number of studies have suggested that the occurrence and progression of HCC were associated with the abnormal expression of many oncogenes and the inactivation of cancer suppressor genes, which were increasingly used in the early diagnosis and treatment of HCC [3,4].…”
Section: Introductionmentioning
confidence: 99%